The seismic structure of Precambrian and early Palaeozoic terranes in the Lambert Glacier region, East Antarctica - Reading, AM (Elsevier, 2006)
The Lambert Glacier region of East Antarctica encompasses the proposed boundary between three of the ancient continents that formed East Gondwana: Indo-Antarctica, the central East Antarctic Craton and a proposed extension of the Pinjarra Orogen of Australia. The only area of extensive rock exposure in central East Antarctica, it uniquely allows the seismic structure to be linked to surface geology. New broadband seismic stations were established at the remote sites of the SSCUA deployment, which ran between the austral summers of 2002/2003 and 2004/ 2005. Recorded energy from distant earthquakes is used to calculate receiver function waveforms that are then modelled to deduce the seismic structure of the upper lithosphere. The results of this study are two-fold. Firstly, seismic structure and crustal depth are determined beneath the Lambert Glacier region providing constraints on its tectonic evolution. A significant contrast in crustal depth is found between the Northern and Southern Prince Charles Mountains that may indicate the location of a major tectonic boundary. Secondly, baseline seismic receiver structures are established for the Rayner, Fisher and Lambert terranes that may be traced beneath the Antarctic ice sheet in the future. 2006 Elsevier B.V. All rights reserved.